Fiber reinforced composite
A fiber-reinforced composite material using alicyclic epoxy compounds and epoxidized vegetable oil maintains strength and reduces environmental impact, addressing the flexibility issue in conventional materials.
Patent Information
- Application Number
- CN202410800431.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-26
- Filing Date
- 2024-06-20
- Publication Date
- 2024-12-27
AI Technical Summary
Conventional fiber-reinforced composite materials face a challenge in maintaining strength when increasing the biomass ratio, leading to increased flexibility that is unsuitable for automotive applications.
A fiber-reinforced composite material comprising a matrix resin made from a combination of an alicyclic epoxy compound and epoxidized vegetable oil, which includes a curing agent and accelerator, is used to enhance strength while maintaining environmental friendliness.
The composite material achieves excellent strength and reduced environmental impact, with a biomass ratio of 5-25% by mass, suitable for automotive parts.
Smart Images

Figure CN119192773A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to fiber reinforced composite parts. Background Art
[0002] In recent years, there has been an active push for sustainable transportation systems that can be used by traffic participants, especially vulnerable groups such as the elderly, the disabled, and children. To achieve this goal, efforts have been made to further improve traffic safety and convenience through developments related to increasing vehicle body rigidity.
[0003] Recently, there is an increasing demand for fiber-reinforced composite materials that can contribute to weight reduction of vehicle bodies and impart more excellent rigidity to the vehicle bodies.
[0004] As a fiber-reinforced composite material applicable to automobile parts, a fiber-reinforced composite material containing reinforcing fibers in a cured product of a resin composition containing a bisphenol F-type epoxy resin is known (for example, see Patent Document 1). According to such a fiber-reinforced composite material, since the bisphenol F-type epoxy resin is cured at a relatively low temperature, it is expected that the productivity of automobile parts using the material can be improved.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2006-265434. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Furthermore, among automobile parts, research has been conducted on parts made of materials that take the environment into consideration in addition to productivity.
[0010] Therefore, it is considered to replace part of the curing components in the fiber-reinforced composite material with plant-derived components, that is, to increase the so-called biomass ratio.
[0011] However, conventional fiber-reinforced composite materials (see, for example, Patent Document 1) have a problem in that the flexibility is significantly increased when the biomass ratio is increased, and the strength required for application as automotive component materials cannot be achieved.
[0012] The present invention aims to provide a fiber-reinforced composite material that includes environmentally friendly materials and exhibits excellent strength, and further contributes to the development of a sustainable transportation system.
[0013] Means used to solve problems
[0014] The fiber-reinforced composite material of the present invention for achieving the above-mentioned objects is characterized by comprising a matrix resin composed of a combination of an alicyclic epoxy compound and an epoxidized vegetable oil.
[0015] Effects of the Invention
[0016] According to the present invention, it is possible to provide a fiber-reinforced composite material that includes environmentally friendly materials and exhibits excellent strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the relationship between the biomass ratio (%) and the strength (MPa) in a cured product of a base resin containing an alicyclic epoxy compound and an epoxidized vegetable oil.
[0018] Figure 2 This is a graph showing the relationship between the biomass ratio (%) and the elastic modulus (MPa) in a cured product of a base resin containing an alicyclic epoxy compound and an epoxidized vegetable oil.
[0019] Figure 3 This is a graph showing the relationship between the biomass ratio (%) and the strength (MPa) in the fiber-reinforced composite material of the present invention. DETAILED DESCRIPTION
[0020] Next, a mode for implementing the fiber-reinforced composite material of the present invention will be described in detail.
[0021] The fiber-reinforced composite material of the present embodiment includes a cured matrix resin and reinforcing fibers. The cured matrix resin includes an alicyclic epoxy compound and an epoxidized vegetable oil.
[0022] As the alicyclic epoxy compound, it is assumed that the compound has at least one cyclic aliphatic group having four or more and seven members in the molecule and has at least two epoxy groups in the molecule. Specifically, it is assumed that the alicyclic epoxide is epoxidized from a compound having a cycloalkane ring.
[0023] As the alicyclic epoxy compound, an alicyclic epoxy compound having two or more alicyclic epoxy groups such as 3,4-epoxycyclohexyl group can be used.
[0024] Furthermore, the alicyclic epoxy groups in such an alicyclic epoxy compound may be bonded to each other via a single bond or via a linking group.
[0025] The connecting group that bonds the alicyclic epoxy groups to each other is not particularly limited, and examples thereof include a divalent hydrocarbon group, a carbonyl group (-CO-), an ether bond (-O-), an ester bond (-COO-), a carbonate bond (-OCOO-), and a group formed by a combination thereof. Examples of the divalent hydrocarbon group include a linear or branched alkyl group having 1 to 6 carbon atoms, or a divalent alicyclic hydrocarbon group.
[0026] Specific examples of alicyclic epoxy compounds include, for example, 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate, tetrahydroindene diepoxide, 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4.1.0]heptane, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, bis(3,4-epoxycyclohexylmethyl)adipate, 3,4,3',4'-diepoxybicyclohexane, dicyclopentadiene dioxide, bis(2,3-epoxycyclopentyl) ether, etc., but are not limited thereto.
[0027] Among them, preferably, the ratio of the cyclic structure of the alicyclic epoxy compound is one cyclic structure for a molecular weight of 140 or less. In other words, the alicyclic epoxy compound preferably has at least one alicyclic group per 140 molecular weight in the alicyclic epoxy compound, calculated as the molecular weight of the cyclic aliphatic group obtained by the total atomic weight of carbon atoms and hydrogen atoms (carbon atoms, hydrogen atoms and oxygen atoms in the case of an alicyclic epoxy group) constituting the alicyclic group in the molecular weight of the alicyclic epoxy compound.
[0028] In addition, preferably, the epoxy equivalent of the alicyclic epoxy compound is less than or equal to 194 (g / eq). In addition, the epoxy equivalent refers to the mass (g / eq) of a resin containing 1 gram equivalent of epoxy groups.
[0029] In addition, the alicyclic epoxy compound is preferably a difunctional or higher-functional compound.
[0030] In addition, the alicyclic epoxy compound is preferably in a liquid state at room temperature (25° C.).
[0031] The alicyclic epoxy compounds described above may be used alone or in combination of two or more.
[0032] Furthermore, commercially available alicyclic epoxy compounds may also be used.
[0033] Specifically, 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate (CEL2021P produced by Daicel Chemical Co. [viscosity 250 mPa·s, epoxy equivalent 130 g / eq]), tetrahydroindene diepoxide (THI-DE produced by ENEOS [viscosity 20 mPa·s, epoxy equivalent 80 g / eq]), 1-methyl-4-(2-methyloxiranyl)-7-oxabicyclo[4.1.0]heptane (dipentene dioxide produced by ARKEMA [viscosity 200 mPa·s, epoxy equivalent 84 g / eq]), etc. can be listed.
[0034] The epoxidized vegetable oil is obtained, for example, by epoxidizing a vegetable oil.
[0035] Examples of the vegetable oil include, but are not limited to, soybean oil, linseed oil, sunflower seed oil, tung oil, castor oil, corn oil, rapeseed oil, sesame oil, olive oil, palm oil, grape seed oil, rice bran oil, cottonseed oil, and safflower seed oil.
[0036] Epoxidized vegetable oils are obtained by epoxidizing the unsaturated groups of unsaturated fatty acid triglycerides of glycerol. In natural oils and fats, triglycerides rarely contain only the same fatty acids, but are composed of a variety of fatty acids.
[0037] The above-mentioned epoxidized vegetable oils may be used alone or in combination of two or more.
[0038] Commercially available epoxidized vegetable oils may be used. Examples of commercially available epoxidized vegetable oils include epoxidized soybean oil (ADK CIZER O-130P manufactured by ADEKA Corporation) and epoxidized linseed oil (ADK CIZER O-180A manufactured by ADEKA Corporation).
[0039] The base resin comprising the alicyclic epoxy compound and the epoxidized vegetable oil may further comprise a curing agent and a curing accelerator.
[0040] Examples of the curing agent include polyamine compounds such as diethylenetriamine, triethylenetetramine, diaminodiphenylmethane, meta-phenylenediamine, and dicyandiamide; polyphenol compounds such as bisphenol A, phenol novolac resin, cresol novolac resin, bisphenol A novolac resin, and phenol aralkyl resin; acid anhydrides such as phthalic anhydride and pyromellitic anhydride; carboxylic acid compounds; active ester compounds, and the like.
[0041] Examples of the curing accelerator include imidazole-based curing accelerators, tertiary amine-based curing accelerators, and phosphorus-based curing accelerators.
[0042] Examples of the reinforcing fibers include glass fibers, carbon fibers, polyester fibers, polyamide fibers, and alumina fibers.
[0043] Next, a method for producing a fiber-reinforced composite material in this embodiment will be described.
[0044] The manufacturing method in the present embodiment mainly comprises a step of preparing a matrix resin and a step of molding a fiber-reinforced composite material by solidifying the matrix resin containing reinforcing fibers in a predetermined mold.
[0045] In the preparation process of the base resin, the alicyclic epoxy compound, the epoxidized vegetable oil, the curing agent and the curing accelerator are mixed and deaerated.
[0046] The content of the epoxidized vegetable oil in the matrix resin (biomass ratio) is preferably set to 5% by mass or more and 25% by mass or less. A matrix resin with such a biomass ratio can effectively reduce the environmental load compared with the past, and its cured product has good flexural strength and flexural modulus.
[0047] Furthermore, it is preferred that the mass ratio (B / A) of the epoxidized vegetable oil (B) to the alicyclic epoxy compound (A) in the base resin exceeds 0 and is 1.2 or less.
[0048] The amount of the curing agent added to the matrix resin can be set to 40 parts by mass or more and 60 parts by mass or less relative to 100 parts by mass of the total mass of the matrix resin.
[0049] The amount of the curing accelerator added to the matrix resin can be set to be 0 parts by mass or more and 3 parts by mass or less relative to 100 parts by mass of the total mass of the matrix resin.
[0050] As a method for molding a fiber-reinforced composite material using such a matrix resin, various known methods can be adopted depending on the intended use and function of the fiber-reinforced composite material.
[0051] The molding method of the fiber-reinforced composite part may be a method of molding a prepreg in which the matrix resin composition is impregnated in advance into the reinforcing fibers, such as the WET stamping method. In addition, the molding method of the fiber-reinforced composite part may be a method of compounding the reinforcing fibers and the matrix resin composition while molding, such as the resin transfer molding method and the resin film infiltration molding method.
[0052] The mass ratio of the reinforcing fibers to the matrix resin in the fiber-reinforced composite material of the present embodiment is assumed to be 1:1, but the present invention is not limited thereto.
[0053] Such a fiber-reinforced composite material of the present embodiment can be used as a material constituting parts of moving bodies such as vehicles, ships, and aircraft. In particular, the fiber-reinforced composite material can be suitably used for automobile parts.
[0054] <Effects>
[0055] Next, the effects of the fiber-reinforced composite material of this embodiment will be described.
[0056] The fiber-reinforced composite material of the present embodiment includes a matrix resin composed of a combination of an alicyclic epoxy compound and an epoxidized vegetable oil.
[0057] According to the fiber-reinforced composite material of the present embodiment, the epoxidized vegetable oil is included, so that the structure is considered for carbon neutrality. In addition, the fiber-reinforced composite material of the present embodiment can achieve both reduction of environmental load and maintenance of good component application strength through the synergistic effect of the alicyclic epoxy compound having a rigid molecular skeleton and the epoxidized vegetable oil that imparts toughness to the fiber-reinforced composite material.
[0058] In addition, it is preferable that the ratio of the cyclic structure in the alicyclic epoxy compound of the fiber-reinforced composite material of the present embodiment is such that one cyclic structure exists for a molecular weight of 140 or less.
[0059] According to such a fiber-reinforced composite material, since the rigidity of the molecular skeleton can be ensured, it is possible to exhibit more excellent strength.
[0060] In addition, the alicyclic epoxy compound of the fiber-reinforced composite material of the present embodiment preferably has an epoxy equivalent of 194 (g / eq) or less.
[0061] According to such a fiber-reinforced composite material, the crosslinking density can be further increased, and more excellent strength can be exhibited.
[0062] In addition, the alicyclic epoxy compound of the fiber-reinforced composite material of the present embodiment is preferably a multifunctional epoxy compound, and the three-dimensional crosslinking is preferably bifunctional or more.
[0063] This fiber-reinforced composite material has a three-dimensional cross-linked structure and can therefore exhibit superior strength.
[0064] In addition, the alicyclic epoxy compound of the fiber-reinforced composite material of the present embodiment is preferably in a liquid state in an uncured state at room temperature.
[0065] According to such a fiber-reinforced composite material, since fluidity can be imparted to the uncured matrix resin, it can be efficiently manufactured by resin transfer molding (RTM) and WET press molding, thereby further improving the cost performance and manufacturability of the fiber-reinforced composite material.
[0066] In the fiber-reinforced composite material of the present embodiment, the biomass ratio of the epoxidized vegetable oil in the matrix resin is preferably 5% by mass to 25% by mass.
[0067] According to such a fiber-reinforced composite material, it is possible to more effectively reduce environmental load and maintain good component application strength.
[0068] Based on the above, the fiber-reinforced composite material of the present embodiment can be suitably used for automobile parts and the like.
[0069] [Example]
[0070] Next, examples and comparative examples for verifying the effects of the fiber-reinforced composite material of the present embodiment will be described.
[0071] (Example 1)
[0072] In this example, 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate (CEL2021P produced by Daicel) was prepared as an alicyclic epoxy compound. This alicyclic epoxy compound has two ring structures, a molecular weight of 252, a viscosity (25° C.) of 250 mPa·s, and an epoxy equivalent of 130 (g / eq).
[0073] In addition, epoxidized soybean oil (ADK CIZER O-130P manufactured by ADEKA Corporation) was prepared as the epoxidized vegetable oil.
[0074] Next, a liquid matrix resin having a biomass ratio of 25% by mass was prepared by mixing 26 parts by mass of an alicyclic epoxy compound, 25 parts by mass of an epoxidized vegetable oil, 49 parts by mass of a curing agent, and 1 part by mass of a curing accelerator. Methyl-3,6-endomethylene-1,2,3,6-tetrahydrophthalic anhydride (MHAC-P manufactured by Showa Denko Materials Co., Ltd.) was used as the curing agent. Tris-dimethylaminomethylphenol (DMP-30 manufactured by Nacalai Tesque Co., Ltd.) was used as the curing accelerator.
[0075] After vacuum degassing, the matrix resin was injected into a mold having a thin-walled cavity with a thickness of 2 mm and cured at a curing temperature of 140° C. and a curing time of 2 hours.
[0076] The cured product of the matrix resin was subjected to a bending strength test and a bending elastic modulus test. The bending strength test and the bending elastic modulus test were conducted in accordance with JIS K7171. The bending strength of the cured product was 47 MPa. The bending elastic modulus of the cured product was 1471 MPa. The results are shown in Table 1. Figure 1 and Figure 2 .
[0077] [Table 1]
[0078]
[0079] Next, a fiber-reinforced composite material is prepared using the uncured aforementioned matrix resin.
[0080] In the process of producing the fiber-reinforced composite material, first, five layers of glass cloth (WR570 produced by Owens Corning) prepared as reinforcing fibers were stacked.
[0081] The laminated glass cloth is coated with and impregnated with a matrix resin having the same weight as that of the glass cloth.
[0082] After vacuum degassing the glass cloth containing the matrix resin, the glass cloth was molded in a mold having a thin-walled cavity with a thickness of 2 mm and cured to obtain a fiber reinforced composite (hereinafter sometimes referred to as FRP: Fiber Reinforced Plastics). The curing temperature was 140°C and the curing time was 2 hours.
[0083] The fiber reinforced composite material (FRP) was subjected to a bending strength test in the same manner as described above. The bending strength of the fiber reinforced composite material (FRP) was 457 MPa. The results are shown in Tables 1 and Figure 3 .
[0084] (Example 2)
[0085] 24 parts by mass of tetrahydroindene diepoxide (THI-DE manufactured by ENEOS) was used as an alicyclic epoxy compound instead of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as an alicyclic epoxy compound in Example 1. In addition, the amount of the curing agent used was changed from 49 parts by mass to 50 parts by mass. In the same manner as in Example 1, a liquid base resin having a biomass ratio of 25% by mass was prepared.
[0086] It should be noted that tetrahydroindene diepoxide has two ring structures, a molecular weight of 154, a viscosity (25° C.) of 20 mPa·s, and an epoxy equivalent of 80 (g / eq).
[0087] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0088] The flexural strength of the cured product was 59 MPa. The flexural modulus of the cured product was 1638 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 520 MPa. The results are shown in Table 1 and Figure 3 .
[0089] (Example 3)
[0090] The amount of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate used as the alicyclic epoxy compound in Example 1 was changed from 26 parts by mass to 22 parts by mass. 25 parts by mass of epoxidized linseed oil (ADK CIZER O-180A produced by ADEKA) was used instead of 25 parts by mass of epoxidized soybean oil as the epoxidized vegetable oil in Example 1. In addition, the amount of the curing agent used was changed from 49 parts by mass to 52 parts by mass. In the same manner as in Example 1, a liquid base resin having a biomass ratio of 25% by mass was prepared.
[0091] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0092] The flexural strength of the cured product was 77 MPa. The flexural modulus of the cured product was 3481 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 652 MPa. The results are shown in Table 1 and Figure 3 .
[0093] (Comparative Example 1)
[0094] Instead of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as the alicyclic epoxy compound in Example 1, 52 parts by mass of a bisphenol A type epoxy compound (828 (epoxy equivalent 192) produced by Mitsubishi Chemical Corporation) was used. No epoxidized vegetable oil was used. In addition, the amount of the curing agent used was changed from 49 parts by mass to 48 parts by mass. In addition, a liquid base resin having a biomass ratio of 0% by mass was prepared in the same manner as in Example 1.
[0095] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0096] The flexural strength of the cured product was 96 MPa. The flexural modulus of the cured product was 3391 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 927 MPa. The results are shown in Table 1 and Figure 3 .
[0097] (Comparative Example 2)
[0098] In place of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as the alicyclic epoxy compound in Example 1, 43 parts by mass of a bisphenol A type epoxy compound (828 (epoxy equivalent 192) produced by Mitsubishi Chemical Corporation) was used. The amount of epoxidized soybean oil used as the epoxidized vegetable oil in Example 1 was changed from 25 parts by mass to 10 parts by mass. In addition, the amount of the curing agent used was changed from 49 parts by mass to 46 parts by mass. In the same manner as in Example 1, a liquid base resin having a biomass ratio of 10% by mass was prepared except for the above.
[0099] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0100] The flexural strength of the cured product was 101 MPa. The flexural modulus of the cured product was 2658 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 810 MPa. The results are shown in Table 1 and Figure 3 .
[0101] (Comparative Example 3)
[0102] 29 parts by mass of bisphenol A type epoxy compound (828 (epoxy equivalent 192) manufactured by Mitsubishi Chemical Corporation) was used instead of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as the alicyclic epoxy compound in Example 1. In addition, the amount of the curing agent used was changed from 49 parts by mass to 45 parts by mass. In the same manner as in Example 1, a liquid base resin having a biomass ratio of 25% by mass was prepared except for the above.
[0103] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0104] The flexural strength of the cured product was 10 MPa. The flexural modulus of the cured product was 411 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 319 MPa. The results are shown in Table 1 and Figure 3 .
[0105] (Comparative Example 4)
[0106] In place of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as the alicyclic epoxy compound in Example 1, 7 parts by mass of a bisphenol A type epoxy compound (828 (epoxy equivalent 192) produced by Mitsubishi Chemical Corporation) was used. The amount of epoxidized soybean oil used as the epoxidized vegetable oil in Example 1 was changed from 25 parts by mass to 50 parts by mass. Furthermore, the amount of the curing agent used was changed from 49 parts by mass to 43 parts by mass. In addition, a liquid base resin having a biomass ratio of 50% by mass was prepared in the same manner as in Example 1.
[0107] An attempt was made to produce a molded body of a cured product and a fiber reinforced composite material (FRP) in the same manner as in Example 1 except that such a matrix resin was used.
[0108] The curing of the matrix resin was insufficient and the bending strength could not be measured. In addition, the bending modulus was 10 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite is 7 MPa. The results are shown in Table 1 and Figure 3 .
[0109] (Comparative Example 5)
[0110] 27 parts by mass of bisphenol A type epoxy compound (828 (epoxy equivalent 192) produced by Mitsubishi Chemical Corporation) was used instead of 26 parts by mass of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate as the alicyclic epoxy compound in Example 1. In addition, the amount of the curing agent used was changed from 49 parts by mass to 48 parts by mass. A liquid base resin having a biomass ratio of 25% by mass was prepared in the same manner as in Example 1.
[0111] A molded body of a cured product and a fiber reinforced composite material (FRP) were prepared in the same manner as in Example 1 except that such a matrix resin was used.
[0112] The flexural strength of the cured product was 30 MPa. The flexural modulus of the cured product was 924 MPa. The results are shown in Table 1. Figure 1 and Figure 2 The bending strength of the fiber reinforced composite (FRP) is 330 MPa. The results are shown in Table 1 and Figure 3 .
[0113] (Reference example)
[0114] The amount of 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate used as the alicyclic epoxy compound in Example 2 was changed from 24 parts by mass to 47 parts by mass. No epoxidized vegetable oil was used. In addition, the amount of the curing agent used was changed from 50 parts by mass to 52 parts by mass. In addition, a liquid base resin having a biomass ratio of 0% by mass was prepared in the same manner as in Example 2.
[0115] Except for using this matrix resin, the same method as in Example 2 was used to prepare a molded body of the cured product and a fiber reinforced composite material (FRP). The results are shown in Tables 1 and Figure 1 .
[0116] (Evaluation of fiber-reinforced composite parts)
[0117] As shown in Table 1 and Figures 1 to 3 As shown in the figures, the cured products of the matrix resin containing the alicyclic epoxy compound of Examples 1 to 3 exhibited good flexural strength and flexural modulus even when the biomass ratio reached 25% by mass, which is the certification standard of the Japan Bioplastics Association (JBPA). In addition, the fiber-reinforced composite material containing the matrix resin and the reinforcing fiber exhibited good flexural modulus.
[0118] On the other hand, the base resins and fiber-reinforced composites of Comparative Examples 3 and 5, which contained bisphenol A-type epoxy compounds instead of alicyclic epoxy compounds, were insufficient in both bending strength and bending elastic modulus. In particular, in the comparison between Example 2 and Comparative Example 3 using epoxidized soybean oil, the bending elastic modulus of the fiber-reinforced composite of Example 2 showed a value 4 times that of the fiber-reinforced composite of Comparative Example 3. In addition, in the comparison between Example 3 and Comparative Example 5 using epoxidized linseed oil, the bending elastic modulus of the fiber-reinforced composite of Example 3 showed a value 3.8 times that of the fiber-reinforced composite of Comparative Example 5.
[0119] Based on the above, it is proved that the fiber-reinforced composite material of the present invention can achieve both reduced environmental load and good strength.
[0120] Although the embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments and can be implemented in various forms.
Claims
1. A fiber-reinforced composite part, characterized in that: Contains a base resin composed of a combination of a cycloaliphatic epoxy compound and an epoxidized vegetable oil.
2. The fiber-reinforced composite component according to claim 1, characterized in that: The ratio of the cyclic structure of the alicyclic epoxy compound is such that one cyclic structure is present in a molecular weight of 140 or less.
3. The fiber-reinforced composite component according to claim 1, characterized in that: The epoxy equivalent of the alicyclic epoxy compound is 194 g / eq or less.
4. The fiber-reinforced composite component according to claim 1, characterized in that: The alicyclic epoxy compound is a multifunctional epoxy compound, and the three-dimensional crosslinking is bifunctional or more.
5. The fiber-reinforced composite component according to claim 1, characterized in that: The alicyclic epoxy compound is in liquid state in an uncured state at room temperature.
6. The fiber-reinforced composite component according to claim 1, characterized in that: The biomass ratio defined by the content of the epoxidized vegetable oil in the base resin is 5% to 25%.
7. The fiber-reinforced composite component according to claim 1, characterized in that: The fiber-reinforced composite part is an automobile component.
Citation Information
Patent Citations
Epoxy resin composition and fiber-reinforced composite material
JP2006265434A
